Evaluation of Dietary Phytogenics on Growth Performance, Carcass Characteristics, and Economics of Grow-finish Pigs Housed Under Commercial Conditions - J. Soto; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 1,260 pigs (PIC 327 × 1050, initially 48.7 lb) were used in a 125-d trial to determine the effect of two dietary essential oil mixtures on the growth performance, carcass characteristics, and economics of finishing pigs. Pigs were allotted by BW and randomly assigned to 1 of 5 dietary treatments. Pigs were fed six dietary phases. Treatment 1 was the control with no feed additives and 12% of CP in the Phase 6 diet. Treatment 2 was the same formulation as treatment 1 but contained an essential oil mixture 1 (EOM 1) containing caraway, garlic, thyme, and cinnamon fed all phases. Treatment 3 was the same formulation as treatment 1 with EOM 1 fed from Phases 3 to 6 and essential oil mixture 2 (EOM 2) containing oregano, citrus, and anise fed all phases (EOM 1+2). Treatment 4 contained EOM 1 fed in all 6 phases with 16% CP in Phase 6. Treatment 5 contained ractopamine HCl (9 g/ton) with 16% CP in the Phase 6 diet. Overall (d 0 to 125), pigs fed diets with EOM 1+2 had increased (P = 0.003) ADFI compared with pigs fed the control treatment. Pigs fed the diet with EOM 1 and 16% CP had increased (P = 0.032) ADFI in comparison with the pigs fed ractopamine HCl treatment. Pigs fed the ractopamine HCl treatment had improved (P = 0.028) F/G compared with pigs fed the treatment with the EOM 1 and 16% CP and the control treatment. For carcass traits, pigs fed the treatment with EOM 1+2 and had increased (P = 0.007) HCW compared with pigs fed EOM 1 and 12% CP and the control treatment (P = 0.002). Pigs fed the treatment with ractopamine HCl also had heavier (P = 0.001) HCW compared with the control treatment. Pigs fed diets with EOM 1+2 had increased (P = 0.001) carcass ADG, compared with pigs fed the control treatment and the treatment with EOM 1 and 12% CP (P = 0.019). Pigs fed the treatment with ractopamine HCl also had improved (P = 0.001) carcass ADG compared with pigs fed the control treatment. Pigs fed diets with EOM 1+2 had increased (P = 0.021) carcass yield compared with pigs fed the treatment with EOM 1 and 12% CP. Carcass yield was improved (P = 0.036) for the treatment with ractopamine HCl in comparison with the control treatment. Economically, feed cost per pound of gain was lower (P<0.001) for pigs fed the control treatment compared to the treatment with EOM 1+2 and pigs fed with the ractopamine HCl treatment. Pigs fed diets with EOM 1+2 or ractopamine HCl treatment had increased (P = 0.001) gain value compared with pigs fed the control treatment. Pigs fed the ractopamine HCl treatment had increased income over feed cost in comparison with the treatments containing EOM 1 with 16% CP. In conclusion, the addition of EOM 1+2 improved ADFI, HCW, carcass ADG, and gain value in comparison with the control treatment. However, the increase in gain was not sufficient to overcome the increase in feed cost. The gain value improvement for the regimen with ractopamine HCl compensated for the extra feed cost resulting in a higher income over feed cost compared with the treatment with EOM 1 and 16% CP.
Keywords: essential oils; feed additives; phytogenics